An Evaluation of Effects of Different Mydriatics on Choroidal Thickness by Examining Anterior Chamber Parameters: The Scheimpflug Imaging and Enhanced Depth Imaging-OCT Study - İsa Yuvacı; Emine Pangal; Sümeyra Yuvacı; Nurettin Bayram; Mustafa Ataş; Burhan Başkan; Süleyman Demircan; Ali Akal (Journal of Ophthalmology)
Aim. To assess the effects of mydriatics commonly used in clinical practice on choroidal thickness and anterior chamber change. Methods. This was a prospective, randomized, controlled, double-blinded study including a single eye of the participants. The subjects were assigned into 4 groups to receive tropicamide 1%, phenylephrine 2.5%, cyclopentolate 1%, and artificial tears. At the baseline, anterior chamber parameters were assessed using a Pentacam Scheimpflug camera system, and choroidal thickness (CT) was measured using a spectral-domain OCT with Enhanced Depth Imaging (EDI) modality. All measurements were repeated again after drug administration. Results. Increases in pupil diameter, volume, and depth of anterior chamber were found to be significant (p=0.000, p=0.000, and p=0.000, resp.), while decreases in the choroidal thickness were found to be significant in subjects receiving mydriatics (p<0.05). Conclusions. The study has shown that while cyclopentolate, tropicamide, and phenylephrine cause a decrease in choroidal thickness, they also lead to an increase in the volume and depth of anterior chamber. However, no correlation was detected between anterior chamber parameters and choroidal changes after drug administration. These findings suggest that the mydriatics may affect the choroidal thickness regardless of anterior chamber parameters. This study was registered with trial registration number 2014/357.